Socio-economic Impact of Flue-Cured Tobacco in Northern Light Soils Zone of Andhra Pradesh - Hema Baliwada , D. Damodar Reddy , S. Kasturi Krishna , Y. Subbaiah and N. Aruna Kumari, (Indian Journal of Extension Education, 2018)
The present study attempts to assess the impact of FCV (Flue Cured Virginia) tobacco crop on socio-economic transformation of tobacco farmers in NLS (Northern Light Soils) zone of Andhra Pradesh. A total of 10 villages were selected by purposive sampling representing progressive tobacco growing villages and non-tobacco growing villages. Twelve farmers were randomly selected from each village so that 60 tobacco and 60 non-tobacco farmers represented the total sample of the study. Tobacco is adequately financed by the banks to an average extent of up to ` 72,000/acre in addition to inputs supplied by Tobacco Board, whereas for other selected crops, the average scale of finance restricted to a maximum limit of ` 30,000/acre. The average net returns per acre of own land is higher for tobacco (` 49,806) than other selected crops grown in the region. The socio-economic impact analysis revealed that tobacco farmers are comparatively having well-furnished houses (38.34%), possession of vehicles like two-wheelers (96.66%), four-wheelers (31.66%), tractors (28.33%), more number of livestock with 5-10 animals (20%), more than one bore well for farm irrigation (11.66%), access to refrigerators (61.66%) in addition to televisions (100%), having bank accounts (100%) and also, access to overseas higher education (11.67%) than non-tobacco growers. The total labour employed per acre for tobacco (131) is comparatively higher than paddy (31), maize (40) and sugarcane (52) including mechanization